Ichnofossils from Cretaceous-Paleogene flysch of Mide locality (Budva zone, Southern Montenegro) - Đaković Martin (Geološki Anali Balkanskoga Poluostrva, 2018)
Cretaceous-Paleogene flysch represents the youngest formation in the Budva Zone. Although the Maastrichtian-Lower Eocene age of these rocks has been well documented in the literature, trace fossils are only mentioned as abundant and not described. In the present paper, only a small number of ichnotaxa from Mide locality has been described, including Lorenzinia carpathica (ZUBER), Nereites irregularis (SCHAFHAUT), Scolicia plana KSIĄŻKIEWICZ and Paleodictyon latum VIALOV & GOLEV. They confirm deepsea environment.